2002
DOI: 10.1590/s0103-90162002000100009
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic light response of the C4 grasses Brachiaria brizantha and B. humidicola under shade

Abstract: Forage grasses in tropical pastures can be subjected to considerable diurnal and seasonal reductions in available light. To evaluate the physiological behavior of the tropical forage grasses Brachiaria brizantha cv. Marandu and B. humidicola to low light, the photosynthetic light response and chlorophyll contents of these species were compared for plants grown outdoors, on natural soil, in pots, in full sunlight and those shaded to 30 % of full sunlight, over a 30-day period. Both species showed the ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2
23

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 13 publications
(13 reference statements)
4
39
2
23
Order By: Relevance
“…Dias-Filho (2002) observed maximum gross leaf photosynthetic rates of 30 µmol CO 2 m -2 s -1 for the grass 'Marandu' in a greenhouse.…”
Section: Gas Exchangementioning
confidence: 82%
“…Dias-Filho (2002) observed maximum gross leaf photosynthetic rates of 30 µmol CO 2 m -2 s -1 for the grass 'Marandu' in a greenhouse.…”
Section: Gas Exchangementioning
confidence: 82%
“…On noninterference, or non-shading, situations, the plant invests on leafs and increases its leaf area index; simultaneously, this greater leaf area confers a greater accumulation of photoassimilates and a resulting higher growth of the roots. On the other hand, when it perceives shading, the plant invests on elongating the cells of the culm, aiming at gaining height and accessing light (Dias-Filho, 2002). In that sense, it was observed that AMFs offer greater height, leaf area and higher radicular growth on coffee plants, which generated a reduction on the biomass accumulation by the U. brizantha plants.…”
Section: Resultsmentioning
confidence: 99%
“…The light compensation point (LCP) for the R biotype was estimated to be 15.84 μmol m -2 s -1 , whereas for the S biotype it was 33.77 μmol m -2 s -1 ( Figure 1B). QY and LCP indicate that the R biotype is more effective in using light energy to assimilate CO 2 and it presents a positive balance in fixing carbon under low luminosity (Dias-Filho, 2002). This may be a competitive advantage for the R biotype in quickly occupying space and establish itself first in the competition, compared to biotype S.…”
mentioning
confidence: 95%